Mysticism, Experience, and Pedagogy in Jewish-Christian Dialogue - Ettin, Andrew V; Wiethaus, Ulrike (Studies in Christian-Jewish Relations, 2011)
The essay presents a dialogic, co-authored reflection on the uses of Jewish and Christian mystical texts in exploring post-Shoah possibilities for Jewish-Christian encounter and dialogue, specifically in the context of the college classroom.The authors explore Buber’s thesis that the heart of each religion is to be found in its mystical dimension, and address the lack of scholarly attention to mystical experience as a dialogic medium of communication and as a means to heal historic trauma.